Peran dan Fungsi DPRD dalam Upaya Pemakzulan Kepala Daerah - Aulia Nisa; Dairani Dairani (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2025)
Dismissal of a Regional Head can occur due to two factors, the first is 'Objective' in investigating violations of the oath or promise of office carried out by the Regional Head. Second, 'Subjective' in using his authority, namely looking for loopholes to dismiss the Regional Head on sentimental grounds. The reasons for the dismissal of a Regional Head are regulated in Article 78 paragraph (1) and paragraph (2) of Law Number 23 of 2014 concerning Regional Government (UUPD). Some of the problems that often occur in the dismissal of Regional Heads are, the Regional Head is elected directly but the mechanism for dismissal is indirectly (representatively) through the DPRD so that it is not in line with democracy, then regional autonomy is not implemented freely because there is still a role for the central government and there is also no Judicial institutions in regions specifically for the dismissal of Regional Heads. After we analyzed the many articles in the Constitution, the amendments relating to the main duties of the House of Representatives, also in UUMD3 1999 in conjunction with UUMD3 2014, were further emphasized by DPR Standing Orders No. 16/DPR/RI/1999-2000 jucto Regulation of the House of Representatives of the Republic of Indonesia Number 1 of 2014 concerning Rules of Procedure, from the authority and duties of the DPRD above, it can be formulated that the DPRD has three functions, namely the supervisory function, the budget function, and the function of making Law or legislation. In carrying out its functions and duties, the DPRD has several rights that can be used to carry out its duties as government supervisor. Some of the rights in question are the Right to Questionnaire, the Right to Interplation, the Right to Express an Opinion. As for the right to inquiry itself, the definition is contained in Article 79 paragraph (3) of Law Number 17 of 2014 concerning the MPR, DPR, DPD and DPRD.